2004
DOI: 10.1126/science.1093891
|View full text |Cite
|
Sign up to set email alerts
|

S -Nitrosylation of Parkin Regulates Ubiquitination and Compromises Parkin's Protective Function

Abstract: Parkin is an E3 ubiquitin ligase involved in the ubiquitination of proteins that are important in the survival of dopamine neurons in Parkinson's disease (PD). We show that parkin is S-nitrosylated in vitro, as well as in vivo in a mouse model of PD and in brains of patients with PD and diffuse Lewy body disease. Moreover, S-nitrosylation inhibits parkin's ubiquitin E3 ligase activity and its protective function. The inhibition of parkin's ubiquitin E3 ligase activity by S-nitrosylation could contribute to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

24
650
5
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 738 publications
(682 citation statements)
references
References 31 publications
24
650
5
3
Order By: Relevance
“…46,47 Our group first identified the physiological relevance of S-nitrosylation by showing that NO and related RNS exert paradoxical effects via redox-based mechanisms -NO is neuroprotective via S-nitrosylation of NMDA receptors (as well as other subsequently discovered targets, including caspases), and yet can also be neurodestructive by formation of peroxynitrite (or, as later discovered, reaction with additional molecules such as parkin, PDI, GAPDH, and MMP-9) (Figure 1). 6,8,9,12,14,16,17,[19][20][21][22]48 Over the past decade, accumulating evidence has suggested that S-nitrosylation can regulate the biological activity of a great variety of proteins, in some ways akin to phosphorylation. 10,[49][50][51][52][53][54] Chemically, NO is often a good 'leaving group,' facilitating further oxidation of critical thiol to disulfide bonds among neighboring (vicinal) cysteine residues or, via reaction with ROS, to sulfenic (ÀSOH), sulfinic (ÀSO 2 H), or sulfonic (ÀSO 3 H) acid derivatization of the protein.…”
Section: Protein S-nitrosylation Affects Neuronal Survivalmentioning
confidence: 99%
See 4 more Smart Citations
“…46,47 Our group first identified the physiological relevance of S-nitrosylation by showing that NO and related RNS exert paradoxical effects via redox-based mechanisms -NO is neuroprotective via S-nitrosylation of NMDA receptors (as well as other subsequently discovered targets, including caspases), and yet can also be neurodestructive by formation of peroxynitrite (or, as later discovered, reaction with additional molecules such as parkin, PDI, GAPDH, and MMP-9) (Figure 1). 6,8,9,12,14,16,17,[19][20][21][22]48 Over the past decade, accumulating evidence has suggested that S-nitrosylation can regulate the biological activity of a great variety of proteins, in some ways akin to phosphorylation. 10,[49][50][51][52][53][54] Chemically, NO is often a good 'leaving group,' facilitating further oxidation of critical thiol to disulfide bonds among neighboring (vicinal) cysteine residues or, via reaction with ROS, to sulfenic (ÀSOH), sulfinic (ÀSO 2 H), or sulfonic (ÀSO 3 H) acid derivatization of the protein.…”
Section: Protein S-nitrosylation Affects Neuronal Survivalmentioning
confidence: 99%
“…Recent findings, however, have shed light on molecular events underlying this relationship. Specifically, we and other groups have recently mounted physiological and chemical evidence that S-nitrosylation enhances (1) neuronal survival by inhibiting the activities of (a) NMDA receptors and (b) caspases, or (2) neuronal cell injury by regulating the (a) ubiquitin E3 ligase activity of parkin, 17,18,20 (b) chaperone and isomerase activities of PDI, 19 (c) nuclear translocation of GAPDH, 21 and (d) activity of MMP-9. 22 In particular, S-nitrosylation of PDI and parkin can regulate protein misfolding and neurotoxicity in models of neurodegenerative disorders, and SNO-PDI, or SNO-parkin has been found in human postmortem brain tissue from patients with neurodegenerative conditions.…”
Section: Protein S-nitrosylation Affects Neuronal Survivalmentioning
confidence: 99%
See 3 more Smart Citations